(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Various types of vitreoretinal surgery are used for the treatment of severe diabetic retinopathy (DR), with vitreous hemorrhage being a common postoperative complication. Impaired angiopoietin system function in type 2 diabetes mellitus (T2DM) patients with DR plays a role in retinal vascular damage and may determine the development of vitreous hemorrhage, e.g., after vitrectomy. Purpose: To identify the effects of angiopoietins on and their prognostic value in the development of vitreous hemorrhage after advanced vitreoretinal surgery in T2DM patients with DR. Material and Methods: The study included 118 T2DM patients (118 eyes) with DR. These included patients with mild nonproliferative DR (NPDR; Group 1; n = 28), moderate or severe NPDR (Group 2; n = 49), and proliferative DR (PDR; Group 3; n = 41). They underwent a 25-G closed subtotal vitrectomy (CSTV) with panretinal laser photocoagulation. Either a mixture of perfluoropropane (18% C3F8) and air was used to perform tamponade of the vitreous cavity or balance salt solution (BSS plus) was left in the vitreous cavity. Vitreous samples were obtained during vitrectomy, and Ang1 and Ang2 concentrations and their ratio for these samples were measured by enzyme-linked immunosorbent assay. Models were developed using the EZR version 1.54 software (Saitama Medical Center, Jichi Medical University, Saitama, Japan), which is a graphical user interface for R (The R Foundation for Statistical Computing; Vienna, Austria). Results: Vitreous hemorrhage developed in 33.1% of patients with T2DM by three months after vitrectomy for DR, and was directly associated with increased levels of Ang1 and Ang2 in the vitreous (p < 0.005). After adjustment for DR severity stage, the risk of postoperative vitreous hemorrhage in patients with mild NPDR was associated with an increased level of Ang2 in the vitreous (OR, 1.95; 95% CI, 1.06-3.59 per 100 pg/ml), with an optimal cut-off point of 1246 pg/ml (р = 0.003). The risk of postoperative vitreous hemorrhage in patients with severe NPDR and PDR was associated with the level of Ang2 as well as the Ang2/ Ang1 ratio in the vitreous. The study identified cut-off vitreous levels of Ang2 of (a) 2806 pg/mL for moderate or severe NPDR (AUC=0.84; 95% CI, 0.71-0.93; p < 0.001) and (b) 4610 pg/mL for PDR (AUC=0.71; 95% CI, 0.55-0.84; p = 0.013). Conclusion: The results obtained demonstrated that Ang2 accumulation in the vitreous resulted in an increased risk of postoperative vitreous hemorrhage, and was of high prognostic significance.